Heart-to-heart: infant heart rate at 3 months is linked to infant-directed speech, mother–infant interaction, and later language outcomes - Endevelt-Shapira, Yaara; Bosseler, Alexis N.; Zhao, T. Christina; Mizrahi, Julia C.; Meltzoff, Andrew N.; Kuhl, Patricia K. (Frontiers in Human Neuroscience, 2024)
Previous studies underscore the importance of speech input, particularly infant-directed speech (IDS) during one-on-one (1:1) parent-infant interaction, for child language development. We hypothesize that infants' attention to speech input, specifically IDS, supports language acquisition. In infants, attention and orienting responses are associated with heart rate deceleration. We examined whether individual differences in infants' heart rate measured during 1:1 mother-infant interaction is related to speech input and later language development scores in a longitudinal study. Using a sample of 31 3month-olds, we assessed infant heart rate during mother-infant face-to-face interaction in a laboratory setting. Multiple measures of speech input were gathered at 3 months of age during naturally occurring interactions at home using the Language ENvironment Analysis (LENA) system. Language outcome measures were assessed in the same children at 30 months of age using the MacArthur-Bates Communicative Development Inventory (CDI). Two novel findings emerged. First, we found that higher maternal IDS in a 1:1 context at home, as well as more mother-infant conversational turns at home, are associated with a lower heart rate measured during mother-infant social interaction in the laboratory. Second, we found significant negative associations between infant heart rate during mother-infant interaction in the laboratory at 3 months and prospective language development (CDI scores) at 30 months of age. Considering the current results in conjunction with other converging theoretical and neuroscientific data, we argue that high IDS input in the context of 1:1 social interaction increases infants' attention to speech and that infants' attention to speech in early development fosters their prospective language growth.